Carnosol Attenuates LPS-Induced Inflammation of Cardiomyoblasts by Inhibiting NF-κB: A Mechanistic in Vitro and in Silico Study. (4th May 2022) - Baradaran Rahimi, Vafa; Momeni-Moghaddam, Mohammad Amin; Chini, Maria Giovanna; Saviano, Anella; Maione, Francesco; Bifulco, Giuseppe; Rahmanian-Devin, Pouria; Jebalbarezy, Ali; Askari, Vahid Reza
Abstract : Carnosol possesses several beneficial pharmacological properties. However, its role in lipopolysaccharide (LPS) induced inflammation and cardiomyocyte cell line (H9C2) has never been investigated. Therefore, the effect of carnosol and an NF- κ B inhibitor BAY 11-7082 was examined, and the underlying role of the NF- κ B-dependent inflammatory pathway was analyzed as the target enzyme. Cell viability, inflammatory cytokines levels (tumor necrosis factor- α (TNF- α ), interleukin (IL)-1 β, IL-6, and prostaglandin E 2 (PGE2 )), and related gene expression (TNF- α, IL-1 β, IL-6, and cyclooxygenase-2 (COX-2)) were analyzed by ELISA and real-time PCR. In addition, docking studies analyzed carnosol's molecular interactions and binding modes to NF- κ B and IKK. We report that LPS caused the reduction of cell viability while enhancing both cytokines protein and mRNA levels (P < 0.001, for all cases). However, the BAY 11-7082 pretreatment of the cells and carnosol increased cell viability and reduced cytokine protein and mRNA levels (P < 0.001 vs. LPS, for all cases). Furthermore, our in silico analyses also supported the modulation of NF- κ B and IKK by carnosol. This evidence highlights the defensive effects of carnosol against sepsis-induced myocardial dysfunction and, contextually, paved the rationale for the next in vitro and in vivo studies aimed to precisely describe its mechanism(s) of action.